(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article analyzes the story “Flower of Hope” by the famous Uzbek writer Khurshid Dostmuhammad, the author focuses on the specificity of creating the image of Fitrat, as well as the author’s skill in creating the image of the writer. The article also examines the role of historical sources in creating the image of the main character, and the interpretations that the writer was guided by.